2008
DOI: 10.15517/rbt.v56i4.5759
|View full text |Cite
|
Sign up to set email alerts
|

Diet, size and reproductive biology of the silver catfish, Chrysichthys nigrodigitatus (Siluformes: Bagridae) in the Cross River, Nigeria

Abstract: The silver catfish, Chrysichthys nigrodigitatus (Lacépède: 1803) is a highly valued food-fish included among the dominant commercial catches exploited in major rivers of Africa. To provide useful biological data for management, samples were collected monthly between January (2005) and December (2007) in three zones: I: Upper Cross River (grassland), II: Middle Cross River (mixed forest and grassland), and III: Lower Cross River (rainforest)] along 200 km length of the Cross River, Nigeria. Data from 1 248 spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 12 publications
5
5
1
Order By: Relevance
“…It can be explained by the fact that the fishing gear was not installed near the breeding grounds [19]. These results are similar to those obtained for the same species in some aquatic ecosystems in Nigeria [19] [31] [47]. However, they differ from those reported by Vanderpuye [17] in Volta Lake.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…It can be explained by the fact that the fishing gear was not installed near the breeding grounds [19]. These results are similar to those obtained for the same species in some aquatic ecosystems in Nigeria [19] [31] [47]. However, they differ from those reported by Vanderpuye [17] in Volta Lake.…”
Section: Discussionsupporting
confidence: 81%
“…Analysis of the sex ratio of C. nigrodigitatus in Lake Togo-Lagoon of Aného showed that the number of males was significantly higher than that of females. It can be explained by the fact that the fishing gear was not installed near the breeding grounds [19]. These results are similar to those obtained for the same species in some aquatic ecosystems in Nigeria [19] [31] [47].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations